Increased Rate of Cesarean Section among Teenage Mothers Attending a Tertiary Teaching Hospital in Indonesia - G Kayika, I Putu; Utama, Teuku K I (Indonesian Journal of Obstetrics and Gynecology, 2017)
Objective: To evaluate adverse obstetrical outcome in teenage pregnancy, and to investigate whether the social factor, demographic factor, and antenatal care is associated with the management of delivery in teenage pregnancy. Methods: A cross-sectional study was conducted by evaluating medical records teenage mothers who went to Dr. Zainoel Abidin Hospital, Banda Aceh, Indonesia during the period of January 2010 to December 2015. Results: From 186 teenage pregnancies, 75 pregnancies was terminated by cesarean section procedures (40.3%). The amount of antenatal care visit was significantly associated with teenage pregnancy (OR 4.14, CI95% 1.86-9.21). The provider of antenatal care, maternal age classification, education, and insurance were not signifcantly associated with management of labour. Conclusion: Teenage pregnancy is associated with higher cesarean section rate. [Indones J Obstet Gynecol 2017; 5-3: 131-134] Keywords: cesarean section, profile, teenage pregnancy